2018
DOI: 10.1016/j.vaccine.2018.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Towards the introduction of pneumococcal conjugate vaccines in Bhutan: A cost-utility analysis to determine the optimal policy option

Abstract: HighlightsPCV13 and PCV10 are both cost-effective in Bhutan.PCV13 yields better health outcomes and slightly more cost than PCV10.Introducing PCV would reduce the workload of scarce medical specialists in Bhutan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…The majority of the studies (n = 10) compared the potential benefits of two newer versions of PCV, namely PCV-10 and PCV-13 [20,25,28,31,34,36,37,42,44,47]. Seven studies assessed the cost-effectiveness of PCV-7 [27,29,30,32,33,39,46], of which one study assessed its effectiveness in the context of typical and pandemic influenza seasons [30].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the studies (n = 10) compared the potential benefits of two newer versions of PCV, namely PCV-10 and PCV-13 [20,25,28,31,34,36,37,42,44,47]. Seven studies assessed the cost-effectiveness of PCV-7 [27,29,30,32,33,39,46], of which one study assessed its effectiveness in the context of typical and pandemic influenza seasons [30].…”
Section: Methodsmentioning
confidence: 99%
“…PCV-13 was assessed in six studies [35,38,40,41,43,45] and comparisons of various types of vaccines were performed in two studies [26,48]. The majority of studies used quality-adjusted life years (QALYs) or disability-adjusted life years (DALYs) as the health outcomes measure [20,25,26,32,[35][36][37][38][39][40][41]44,47,48] while the rest combined both the clinical and the utility outcomes or provided only clinical outcomes, e.g., cases of pneumococcal-related diseases and life years. Three studies performed both a CUA and a budget impact analysis (BIA) [31,37,45], while one study performed CEA and BIA [39].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A health economics analysis was conducted to determine the cost-utility of 10-and 13-valent pneumococcal conjugate vaccines (PCV10 and PCV13) compared to no vaccination in Bhutan [36]. It suggested that PCV13 and PCV10 could prevent 30 and 18 deaths respectively in the vaccinated population.…”
Section: National Preventive Strategiesmentioning
confidence: 99%